Impact of hybrid nanofluids on MHD flow and heat transfer near a vertical plate with ramped wall temperature - Rajesh, Vemula; Sheremet, Mikhail A.; Öztop, Hakan Fehmi (Elsevier, 2021)
Heat transfer augmentation is a modern challenge in various engineering fields including heat exchangers, electronics, chemical and bio reactors, and others. Nanofluids as a new heat transfer liquids can be considered as effective media for increment of energy transport. Such gain is getting due to an increase in the effective thermal conductivity and change in the fluid flow dynamics. In the case of hybrid nanofluids when we can include two or several nanoadditives to the host liquid one can obtain more essential enhancement of transport processes. Therefore, this paper deals with the energy augmentation using hybrid nanofluids. The objective is to find exact analytical solutions to the unsteady hybrid nanofluid flow with heat transfer past an infinite flat vertical plate with a ramped temperature profile concerning time. The effects of various hybrid nanofluids on the unsteady flow and heat transfer features in the presence of the magnetic field, thermal radiation and a temperature-dependent heat source are explored. Results of radiation parameter, heat source parameter, magnetic parameter and nanoparticle volume fraction obtained by employing the Laplace transform technique for engineering variables such as skin friction coefficient and Nusselt number along with velocity and temperature profiles are analyzed using graphs. It has been found that a growth of the average Nusselt number occurs with the nanoparticle volume fraction, while this augmentation can be improved with use of hybrid nanofluid.
Keywords: Laplace transform technique; Hybrid nanofluid; Infinite vertical plate; Ramped temperature; Magnetic field; Heat source; Unsteady flow